2015
DOI: 10.1063/1674-0068/28/cjcp1503042
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion Luminescence from Ho3+ and Yb3+ Codoped α-NaYF4 Single Crystals

Abstract: The Ho 3+ /Yb 3+ co-doped α-NaYF 4 single crystal was grown successfully for the first time by a modified Bridgman method in which KF was used as assisting flux and a large temperature gradient (70−90 • C/cm) of solid-liquid interface was adopted. Upconversion emissions at green ∼544 nm, red ∼657 and ∼751 nm were obtained under 980 nm laser diode excitation. The intensity at ∼544 nm was much stronger than those of ∼657 and ∼751 nm. The mechanisms of the upconversion emissions were investigated by studying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The green emission at approximately 550 nm and the red emission at 650 nm correspond to characteristic transitions of Ho 3+ : 5 F 4 / 5 S 2 → 5 I 8 and 5 F 5 → 5 I 8 , respectively [ 20 , 46 , 47 ]. Previous studies [ 23 , 26 ] have extensively investigated the phenomenon of concentration quenching in UC emission, primarily attributed to an excessive concentration of Yb 3+ . In these studies, it was shown that, when the concentration of Yb 3+ exceeds 10 at%, the concentration quenching becomes evident, leading to a significant decrease in UC emission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The green emission at approximately 550 nm and the red emission at 650 nm correspond to characteristic transitions of Ho 3+ : 5 F 4 / 5 S 2 → 5 I 8 and 5 F 5 → 5 I 8 , respectively [ 20 , 46 , 47 ]. Previous studies [ 23 , 26 ] have extensively investigated the phenomenon of concentration quenching in UC emission, primarily attributed to an excessive concentration of Yb 3+ . In these studies, it was shown that, when the concentration of Yb 3+ exceeds 10 at%, the concentration quenching becomes evident, leading to a significant decrease in UC emission.…”
Section: Resultsmentioning
confidence: 99%
“…Yb 3+ possesses unique features, including outstanding absorption at 980 nm and favorable energy levels matching with those of Ho 3+ ions, making it an excellent sensitizer [ 19 22 ]. The energy transfer mechanism between Yb 3+ and Ho 3+ in α -NaYF 4 with strong green emission and in core–shell β -NaYF 4 nanoparticles with red emission was investigated by Zhang et al [ 23 ] and Pilch et al [ 24 ]. Additionally, numerous UC luminescent matrices co-doped with Yb 3+ and Ho 3+ were thoroughly studied for their potential application in non-thermally coupled temperature sensors based on the LIR technique.…”
Section: Introductionmentioning
confidence: 99%